Lipidomic profiling of high‐fat diet‐induced obesity in mice: Importance of cytochrome P450‐derived fatty acid epoxides. Issue 1 (28th November 2016) - Wang, Weicang; Yang, Jun; Qi, Weipeng; Yang, Haixia; Wang, Chang; Tan, Bowen; Hammock, Bruce D.; Park, Yeonhwa; Kim, Daeyoung; Zhang, Guodong
Abstract : Objective: Enzymatic metabolism of polyunsaturated fatty acids leads to formation of bioactive lipid metabolites (LMs). Previous studies have shown that obesity leads to deregulation of LMs in adipose tissues. However, most previous studies have focused on a single or limited number of LMs, and few systematical analyses have been carried out. Methods: A LC‐MS/MS‐based lipidomics approach was used, which can analyze >100 LMs produced by cyclooxygenase, lipoxygenase, and cytochrome P450 (CYP) enzymes, to analyze the profile of LMs in high‐fat diet‐induced obesity in mice. Results: LC‐MS/MS showed that high‐fat feeding significantly modulated profiles of LMs in adipose tissues. Among the three major polyunsaturated fatty acid metabolizing pathways (cyclooxygenase, lipoxygenase, and CYP), CYP‐derived fatty acid epoxides were the most dramatically altered LMs. Almost all types of fatty acid epoxides were reduced by 70% to 90% in adipose tissues of high‐fat diet‐fed mice. Consistent with the reduced levels of fatty acid epoxides, the gene expression of several CYP epoxygenases, including Cyp2j5, Cyp2j6, and Cyp2c44, was significantly reduced in adipose tissues of high‐fat diet‐fed mice. Conclusions: Results show that CYP‐derived fatty acid epoxides are the most responsive LMs in high‐fat diet‐induced obesity, suggesting that these LMs could play critical roles in obesity.